1993
DOI: 10.1128/aem.59.4.968-973.1993
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of oolong tea polyphenols on glycosyltransferases of mutans Streptococci

Abstract: Oolong tea extract (OTE) was found to inhibit the water-insoluble glucan-synthesizing enzyme, glucosyltransferase I (GTase-I), of Streptococcus sobrinus 6715. The GTase-inhibitory substance in the OTE was purified by successive adsorption chromatography on Diaion HP-21 and HP-20 columns; this was followed by further purification by Sephadex LH-20 column chromatography. A major fraction that inhibited GTase activity (fraction OTF10) was obtained, and the chemical analysis of OTF10 indicated that it was a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
5

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(81 citation statements)
references
References 33 publications
3
72
0
5
Order By: Relevance
“…Therefore, we next examined the inhibitory activity of the compounds on these enzymes. The inhibition of insoluble glucan synthesis >90% obtained with GSE was in agreement with results described for another grape seed extract (Toukairin et al 1991) and for other polyphenolic extracts (Otake et al 1991;Nakahara et al 1993). Numerous studies have identified oligomeric proanthocyanidins (or condensed tannins) as most active in the GTFs inhibition, and one characteristic of the grape seeds is to be rich in these molecules, which could explain the observed results (Nakahara et al 1993).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, we next examined the inhibitory activity of the compounds on these enzymes. The inhibition of insoluble glucan synthesis >90% obtained with GSE was in agreement with results described for another grape seed extract (Toukairin et al 1991) and for other polyphenolic extracts (Otake et al 1991;Nakahara et al 1993). Numerous studies have identified oligomeric proanthocyanidins (or condensed tannins) as most active in the GTFs inhibition, and one characteristic of the grape seeds is to be rich in these molecules, which could explain the observed results (Nakahara et al 1993).…”
Section: Discussionsupporting
confidence: 88%
“…Both tannic acid and the constituents of OTE are polyphenols. However, the molecular weight of the main polyphenolic constituent in OTE (2 kDa) is lower than that of tannic acid (Nakahara et al, 1993). Therefore, the fine structure in cells can be clearly visible with OTE staining, but is slightly obscure with tannic acid staining (Sato et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The active substance present in OTE was determined to be polymeric polyphenols with a molecular mass of 2000, which is not found in green tea extract (GTE). D-(+)-Catechin, a monomeric polyphenol found in GTE, was shown to exhibit only a weak inhibitory effect on GTase activity from mutans streptococci in a dose-dependent fashion [4]. It was later demonstrated that D-(+)-catechin was quickly glucosylated when incubated with GTase and sucrose, which resulted in blockage of GTase inhibitory activities of catechin [5].…”
Section: Mutans Streptococci Includingmentioning
confidence: 99%
“…GTase synthesizing water-insoluble glucan from sucrose was prepared from culture supernatants of S. sobrinus 6715 (serotype g) by ammonium sulfate precipitation as described by Furuta et al [8]. The inhibitory activities of polyphenolic substances against GTase were measured as described previously [4]. Briefly, GTase (50 mu), sucrose (1.0% w/v), dextran TlO (1 .O mg ml-' ; Pharmacia Biotech), and sodium azide (0.1% w/v) in 3.0 ml of 0.1 M phosphate buffer (pH 6.0) was incubated at matic action of peroxidases present in tea leaves.…”
Section: Quantitution Of Glucun Synthesismentioning
confidence: 99%